THE EFFECT OF WORK MOTIVATION AND WORK LIFE BALANCE ON EMPLOYEE PRODUCTIVITY IN STARTUPS IN WEST JAVA - Muhammad Devone Alfarizy; Mugi Puspita (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
Startups in West Java operate in high velocity environments characterized by tight deadlines, rapid change, and flexible working arrangements, which may shape employee productivity. This study examines the effects of work motivation and work life balance on employee productivity among startup employees in West Java, Indonesia. Using a quantitative cross-sectional design, data were collected through a structured questionnaire from 42 startup employees and analyzed using PLS-SEM. The measurement model demonstrated adequate convergent validity with AVE values exceeding 0.50 for all constructs (Employee Productivity is 0.744; Work Life Balance is 0.681; Work Motivation is 0.712, and discriminant validity was supported by HTMT values below 0.85. The structural model explained 17.2% of the variance in employee productivity (R² = 0.172), with acceptable model fit 0.086. The results show that work life balance significantly influences employee productivity (β = −0.421, p = 0.002), while work motivation does not have a significant effect (β = 0.016, p = 0.950). The novelty of this study lies in providing empirical evidence from Indonesian startups showing that productivity is more strongly associated with work life conditions than with general motivation levels in the observed sample. Practically, the findings suggest that startups should implement structured flexibility, strengthen boundary management, and provide supportive leadership to sustain productivity.